2021
DOI: 10.1101/2021.01.19.427273
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

VISUAL network analysis reveals the role of BEH3 as a stabilizer in the secondary vascular development in Arabidopsis

Abstract: During secondary growth in plants, vascular stem cells located in the cambium continuously undergo self-renewal and differentiation throughout the lifetime. Recent cell-sorting technique enables to uncover transcriptional regulatory framework for cambial cells. However, the mechanisms underlying the robust control of vascular stem cells have not been understood yet. By coexpression network analysis using multiple transcriptome datasets of an ectopic vascular cell transdifferentiation system using Arabidopsis c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…5A, B, Supplemental Movie S9,S10). Results showed that the activation of the GH3.1 promoter occurred earlier than that of the NAC004 promoter, which is consistent with findings from the co-expression gene network analysis (Furuya et al, 2021).…”
Section: Spatio-temporal Dynamics Of Vascular Cell Differentiation In...supporting
confidence: 88%
See 4 more Smart Citations
“…5A, B, Supplemental Movie S9,S10). Results showed that the activation of the GH3.1 promoter occurred earlier than that of the NAC004 promoter, which is consistent with findings from the co-expression gene network analysis (Furuya et al, 2021).…”
Section: Spatio-temporal Dynamics Of Vascular Cell Differentiation In...supporting
confidence: 88%
“…2A, Supplemental Movie S3, S4, S5, S6). Quantitative analysis of luminescence intensity revealed that temporal changes of ELUC signals followed similar trends as UBQ14 and AtHB8 expression changes in the VISUAL time-course microarray experiments (Furuya et al, 2021, Supplemental Fig. S7A-D).…”
Section: Spatio-temporal Dynamics Of Cambial Identity Acquisition In ...mentioning
confidence: 73%
See 3 more Smart Citations